Is Venous Thromboembolism Prophylaxis Needed in Patients Undergoing Knee Arthroscopy? A Prospective Observational Study - Joshi, Amit; Rijal, Nishchal; Gurung, Subash; Basukala, Bibek; Sharma, Rajiv; Bista, Rohit; Singh, Nagmani; Pradhan, Ishor (Journal of Nepal Health Research Council, 2024)
Background: Although rare, deep vein thrombosis is a potentially life-threatening complication of knee arthroscopy. There are scanty literature analysing deep vein thrombosis after arthroscopy in Nepal. This study aimed to identify the prevalence of deep vein thrombosis in patients undergoing knee arthroscopy without chemoprophylaxis postoperatively at 2 weeks and 6 weeks, respectively. The study also aimed to estimate the risk of deep vein thrombosis in these patients by using Caprini Risk Assessment Model.Methods: This prospective observational study was conducted at AKB center, B&B Hospital, Gwarko, Lalitpur, over a period of 16 months. All patients who underwent arthroscopy knee surgeries fulfilling the inclusion criteria were included in the study. The primary outcome measure was the prevalence of deep vein thrombosis as diagnosed by compression color-coded ultrasonography of the popliteal vein and calf vein at 2 weeks and 6 weeks postoperatively. The secondary outcome measure was the prevalence of deep vein thrombosis in the risk groups according to Caprini Risk Assessment Model.Results: Out of 612 patients who underwent arthroscopic knee surgeries during the study period, 2 patients (0.33%) developed deep vein thrombosis at 6 weeks follow-up as diagnosed with ultrasonography of the popliteal and calf veins. The prevalence rate in high-risk group was 0.33% (1 in 307) and in very high-risk group was 5.88% (1 in 17).Conclusions: There was a low prevalence of deep vein thrombosis without chemoprophylaxis following knee arthroscopy in our study. There was higher prevalence of deep vein thrombosis in very high-risk group patients, so close monitoring of such patients during follow-up is recommended.Keywords: Caprini Risk Assessment Model; deep vein thrombosis; knee arthroscopy; prevalence.